2019
DOI: 10.1016/j.indcrop.2019.111652
|View full text |Cite
|
Sign up to set email alerts
|

Carum carvi L. essential oil: A promising candidate for botanical herbicide against Echinochloa crus-galli (L.) P. Beauv. in maize cultivation

Abstract: In this study we tested the possibility that foliar-applied caraway or peppermint essential oils (EOs) can selectively inhibit the growth of Echinochloa crus-galli (a typical maize weed) but not that of maize plants, attempting to develop an eco-friendly botanical herbicide.We tested the phytotoxic potential of oil-in-water emulsions of each EO with addition of commercial adjuvant mainly composed of fatty acids methyl esters, studying their effect on 2 visible plants injuries, biomass accumulation, chlorophyll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…EOs physiological impacts have been and can be studied at the metabolomic [113], proteomic [114] and transcriptomic [115] levels and large amounts of untargeted data will emerge by grouping these techniques of research together. As phytotoxicity is either a goal (herbicide) or a constraint (other biopesticidal application or biostimulation), both parts will be discussed separately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EOs physiological impacts have been and can be studied at the metabolomic [113], proteomic [114] and transcriptomic [115] levels and large amounts of untargeted data will emerge by grouping these techniques of research together. As phytotoxicity is either a goal (herbicide) or a constraint (other biopesticidal application or biostimulation), both parts will be discussed separately.…”
Section: Discussionmentioning
confidence: 99%
“…Phytotoxicity towards weeds without affecting the crop is essential to develop selective bio-herbicides. In this regard, the identification of other molecular mechanisms such as sugar and amino acid accumulation to prevent EOs stress seems promising as demonstrated in maize [113].…”
Section: Discussionmentioning
confidence: 99%
“…For a healthy sample, this ratio is around 0.83 and lowers as plant stress increases, reaching 0.3 at the end of senescence ( Bresson et al, 2018 ). Moreover, the maximum quantum yield of photosystem II has been used to evaluate foliar response after EO application ( Synowiec et al, 2015 , 2019 ). Measurements were performed at the same time of day for each time considered ( t = 0, 24, 48, 72, and 96 h for each modality tested).…”
Section: Methodsmentioning
confidence: 99%
“…Concerning the selectivity of the EOs, Synowiec et al [ 93 ] reported that caraway EO emulsion was a good candidate for weed management in corn crops. This EO was selective, severely affecting the physiology and metabolism of E. crus-galli without damaging the corn.…”
Section: Effects Of Eos On Plant Physiology and Mode Of Action Of mentioning
confidence: 99%